Transnational Nepalis’ Pursuit of the American Dream in Sirjana Sharma’s Golden Gate (SCHOLARS: Journal of Arts & Humanities, 2025)
This study examines the pursuit of the American Dream by Nepali immigrants, with a particular focus on transnational Nepalis, in Sirjana Sharma’s Golden Gate. It explores their passion to cross borders and achieve freedom and prosperity, drawing on key scholarly works, including Susan Hangen’s analysis of transnational politics in Nepali organizations, Bandita Sijapati’s research on Nepali transmigrants, and Arun R. Joshi et al.’s study on Nepali migrants’ aspirations in America. The analysis also garners support from Tristen Brusle’s insights into migrant labor and Paul Jay’s Global Matters, which provide a framework for understanding the socio-political, economic, and cultural push factors behind Nepalis’ migration. Centering on the protagonist Mahima’s adolescent dream of migrating abroad, the paper is substantiated by real-world narratives of Nepali migrants’ experiences in their “dream” country. The study investigates the temptation of the United States, mainly made possible by the DV Lottery program, and the ambivalence migrants experience due to the stark contrast between their homeland and the foreign environment. Drawing on evidence from the novel, it concludes that success in the “dream” country is possible only at the cost of emotional detachment from loved ones, cultural alienation, and numerous other challenges to adopt to a completely new milieu.